Study of cultural properties of canine enteric coronavirus isolate in different cell cultures - A. A. Komarova; T. S. Galkina (Ветеринария сегодня)
The etiology of the diseases affecting gastrointestinal tractofdogs is variable. The second most important enteric viral pathogen in the world after parvovirus is coronavirus (CCoV). Vast studies by scientists from different countries evidence the ubiquitous spread of coronavirus infection in dog populations. In this regard, the prevention of this disease is still an acute problem; firstly this means the development of effective vaccines, which can provide are liable protection from the infection. The aim of this work was to study the CCoV isolate cultural properties, the selection of cell cultures most suitable for its reproduction and optimization of virus cultivation parameters in sensitive cell lines. TheCCoV isolate recovered from the pathological material of a dead puppy with enteritis symptoms was used in the study. Seven continuousandtwoprimarytrypsinizedcellculturesweretestedduringthestudyanditwasestablishedthat the most sensitive cell culture for the reproduction of this isolate was continuous Crandell-Rees Feline Kidney Cells (CRFK) in which atypical cytopathic effect was notedon Day 2 of the cultivation. Virus infectivity titer in this culture was 3.58 ± 0.14 lgTCID50/cm3 . It was established that such cell linesas fel in espleen cells (FS) and primary trypsinized kitten spleen cells (KS) are also sensitive to the CCoV isolate but less than CRFK cells. Effect of such parameters as multiplicity of infection, cultivation time, inoculation technique, adsorption period and cell lineag eon coronavirus growth rate was studiedfor some selected cell cultures. It was concluded that CRFK and FS cells can be used for the propagation of viral material to develop diagnostic tools and vaccines against canineenteric coronavirus.